A new methodology for choosing the efficient and optimal option of renewable energy for local heat supply (Journal of Applied Science and Engineering A, 2024)
One of the tendencies of the power engineering sector in Mongolia is to devise an eco-friendly new technology, and solve the problem of supplying heat from reliable sources to consumers in the centralized rural areas of the country. The soil temperature is divided into four different zones. The soil temperature starts from 1.6 meters for the 4th zone, the southern part like the Gobi provinces of Mongolia, where the soil temperature has never decreased, even in the coldest months of the year. The study compared solar collector systems and heat pump systems and proposed environmentally friendly and economically efficient heating technologies depending on the climatic zones of Mongolia.